A CONTRASTIVE ANALYSIS OF IDIOMS DENOTING HUMANS WITH DISPRAISING IMPLICATIONS IN ENGLISH AND VIETNAMESE - Trương Thị Bích Hồng (Trường Đại học Ngoại ngữ, Đại học Đà Nẵng, 2025)
Idioms are diverse and bring a large number of challenges to learners. This paper is carried out to deal with a small part of idioms: the syntactic, stylistic and semantic features of IDHDIE and IDHDIV. The qualitative and quantitative analysis is made with the investigation of 354 English and Vietnamese idioms collected from dictionaries together with a variety of samples from various linguistic books, dictionaries, stories and from the internet. By means of a contrastive analysis, this investigation aims at discovering the syntactic, stylistic and semantic features of IDHDIE and IDHDIV as well as the similarities and differences among these features. IDHDI of both languages reveal the same eighteen topics. Some IDHDIE have Vietnamese equivalents, which prove the two peoples sometimes think in the same way to a certain extent. Although both languages have idioms covering eighteen topics, the number of idioms in each topic is different. Vietnamese idioms on dispraising physical appearance are more diversified and specific than English ones. IDHDIV employ a style rich in images, which use similes in a large number of idioms whereas IDHDIE do not. IDHDIV reveal specific features of Vietnamese culture originating from the wet rice civilization. Images used in comparison in IDHDIE, however, show their daily life in a different way. Vietnamese idioms also show the impact of Buddhism, the religious belief of most of Vietnamese people, on the way people think whereas Western people believe in God. Regional characteristics between the two also show differences. IDHDIV own a few idioms using the names of some regions, which almost have no equivalents in English and vice versa.